Testing the Bending Strength of Carbon Fiber Composites using the vacuum infusion and vacuum bagging method on the UAV Skywalker 1900 Fuselage Material - Chandra Febriyanto; Ferry Setiawan; Ikbal Rizki Putra (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2023)
The purpose of this study was to determine the bending strength of carbon fiber composite materials with lycal epoxy resin on the Skywalker 1900 UAV. Composites will be made for test specimens with carbon fiber combined with lycal resin using vacuum infusion printing and vacuum bagging methods. From these two methods a sample of specimens will be made for testing using a bending test using the three point bending method to determine the bending strength value of the fuselage material. As for another test, namely microphotos, the process of observing this microstructure can find out how the shape, size, and distribution of second phase particles have an important role in knowing the properties of the material itself. The results of the test specimens were compared between vacuum infusion printing and vacuum bagging and then the best value was sought between the two methods. The results were obtained after testing where the two methods of printing and micro-photos obtained the best results in vacuum bagging. In the vacuum bagging process, the highest value was found in specimen b2 with a bending stress value of 1201.90Mpa and the lowest yield was found in specimen i1 with a bending stress value of 1017.74Mpa. Then the micro photo test can be seen in the vacuum bagging printing process, the penetration of the resin in bagging to the fiber is better.